2012
DOI: 10.5090/kjtcs.2012.45.3.192
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the Posterior Mediastinum Extending into the Adjacent Spinal Canal

Abstract: Leiomyosarcoma of the mediastinum and primary leiomyosarcoma of the spine are exceedingly rare. In most cases, spinal leiomyosarcoma is metastatic. In this report, we describe the case of a 58-year-old man who presented with a large leiomyosarcoma of the posterior mediastinum that extended into the adjacent spinal canal. The tumor was completely resected from the mediastinum, but only subtotally removed from the spinal canal because the spinal mass had tightly invaded the spinal cord. Because the patient's pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Mediastinal leiomyosarcoma is a very rare tumour with less than 40 cases described as case reports and in two small series [ 2 , 13 , 34 , 37 , 52 , 72 , 79 , 82 , 90 , 106 , 107 , 111 , 133 , 163 , 187 , 188 , 207 , 228 ]. Mediastinal leiomyosarcoma occurs in adult patients (26–88 years) of either sex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediastinal leiomyosarcoma is a very rare tumour with less than 40 cases described as case reports and in two small series [ 2 , 13 , 34 , 37 , 52 , 72 , 79 , 82 , 90 , 106 , 107 , 111 , 133 , 163 , 187 , 188 , 207 , 228 ]. Mediastinal leiomyosarcoma occurs in adult patients (26–88 years) of either sex.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, an origin from major vessels seemed likely [ 188 , 228 ], whilst in others, major vessels appeared rather entrapped within the tumour. Mediastinal leiomyosarcoma is typically a non-encapsulated, circumscribed mass, which may infiltrate the heart, lungs, thoracic vertebrae or spinal canal [ 34 , 37 , 107 , 133 ]. Patients were treated by surgical resection, sometimes combined with chemo- and/or radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported a similar case of posterior mediastinal LMS that adhered to but did not invade the aorta [10] . The 58-year-old male patient had a biopsy proven low grade posterior mediastinal tumor diagnosis 3 months prior to onset of neurological symptoms, however had opted out of resection at that time for personal reasons.…”
Section: Discussionmentioning
confidence: 95%
“…Leiomyosarcoma is a common subtype of malignant mesenchymal neoplasms, representing about 20% of all newly diagnosed soft tissue sarcomas [7] . LMS occurs more commonly in the abdomen, retroperitoneum, large blood vessels, and uterus and only very rarely in the mediastinum with less than 50 cases reported in the literature [3 , 5 , 6 , 8 , 9 , 10 , 12] . We present an unusual case of posterior mediastinal epithelioid type leiomyosarcoma causing spinal cord compression and edema.…”
Section: Introductionmentioning
confidence: 99%
“…When a leiomyosarcoma is located in the posterior mediastinum, the tumor can push against surrounding organs, such as the esophagus, descending aorta, the spinal canal, and the inferior vena cava, which can occasionally be affected. [ 4 , 7 , 11 , 15 ] When a leiomyosarcoma is located in the anterior mediastinum, the boundary of the lesion is clear and occasionally calcified. [ 4 6 , 14 , 16 ] It may surround the vena cava and form an embolism.…”
Section: Discussionmentioning
confidence: 99%